2012
DOI: 10.3122/jabfm.2012.05.120070
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Tailored Primary Care Program to Reverse Excessive Alcohol Consumption

Abstract: Objectives: To assess the effects of a tailored, multifaceted intervention in primary care on the level of patients' alcohol consumption and to investigate which patient and organizational factors determine a reduction in alcohol consumption.Methods: This was a cluster randomized, controlled trial conducted among primary care practices in The Netherlands. Data from 6318 patients were available, of whom 712 patients from 70 practices were hazardous or harmful alcohol users. The improvement (intervention) progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
1
24
0
2
Order By: Relevance
“…Lack of training, lack of time, lack of motivation, and lack of suitable counselling materials are among the most commonly cited barriers 23,[29][30][31][32][33][34][35][36][37] ; whereas having patients who seek advice for alcohol issues, more training, and ready availability of support services, screening and counselling materials are commonly reported facilitators. 23,30,31,38 Whilst several studies have documented or tested training, financial or other interventions designed to increase the implementation of alcohol SBI in primary care, 26,39 few are theoretically informed 40 and reporting of the content of training and follow up support is often poor. 41 Johnson et al reviewed the barriers and facilitators for implementing alcohol screening and brief intervention in 2009, 42 giving priority to studies judged to best inform the UK practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of training, lack of time, lack of motivation, and lack of suitable counselling materials are among the most commonly cited barriers 23,[29][30][31][32][33][34][35][36][37] ; whereas having patients who seek advice for alcohol issues, more training, and ready availability of support services, screening and counselling materials are commonly reported facilitators. 23,30,31,38 Whilst several studies have documented or tested training, financial or other interventions designed to increase the implementation of alcohol SBI in primary care, 26,39 few are theoretically informed 40 and reporting of the content of training and follow up support is often poor. 41 Johnson et al reviewed the barriers and facilitators for implementing alcohol screening and brief intervention in 2009, 42 giving priority to studies judged to best inform the UK practice.…”
Section: Introductionmentioning
confidence: 99%
“…3,18 Furthermore, of the many patients visiting primary care who are at-risk drinkers, [19][20][21] few currently receive any alcohol-related advice or intervention from their doctor. [22][23][24][25][26][27][28] They are therefore denied the opportunity to understand the risks and make an informed decision about whether or not to cut down.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of physical activity were reduced in one network. Perhaps most interesting is the study reported by Hilbink et al,20 which found that, although a robust, multicomponent quality improvement strategy was associated with a reduced rate of problem drinking, patients in control practices reduced their rate to an even greater extent. The authors propose that regression to the mean and several methodological challenges probably explain these unanticipated results.…”
Section: This Annual Practice-based Research Theme Issue Of the Journmentioning
confidence: 90%
“…59 The impact of an intervention could be unexpected (worse than expected or even harmful). 60 It would be pertinent to analyze the behavior within each group to understand such changes, as was done in a recent cluster study. 61 We integrated characteristics of the general practitioners into our analysis, and are further evaluating patients' behavior according to these characteristics and the practitioners' practices.…”
Section: Strengths and Limitationsmentioning
confidence: 99%